Keterkaitan Jarak Geografis Terhadap Eksistensi Tradisi Pantauan Bunting (Konstruksi Sosial Suku Besemah, Lahat, Indonesia) - Novia Fitri Istiawati; Miranda Agustin Lestari; Sugeng Widodo (Universitas Negeri Gorontalo, 2023)
This study aims to look at the backwardness of the region and the socio-cultural construction of the Besemah Pantauan Bunting tradition by revealing: 1) the process of the birth of the tradition, 2) the factors causing differences in the distribution of traditions in each region, and 3) existence in the tracking era of the Besemah Tribe. The research was conducted in Lahat District, South Sumatra using an interpretive paradigm, qualitative research types, and ethnographic methods. Data was obtained from primary and secondary sources. Data collection techniques were carried out through non-participant observation, interviews, documentation, and purposive sampling techniques. Data analysis was carried out through open coding, axial coding, and selective coding. In contrast, data analysis was carried out through continuous observation, triangulation, member checks, peer reviews, and reference adequacy checks. Based on the results of the study with Berger's social construction theory, social construction is formed through 3 (three) dialectical processes namely, the first externalization of the existence of Pantauan Bunting as part of the Besemah Tribe marriage which is intended to introduce the bride and groom to relatives and family so that a harmonious relationship is established in the period after marriage. Second, the process of objectivation through the implementing regulations for the Pantauan Bunting tradition succeeded in legitimizing the existence of this tradition in society. Third, the process of internalization through primary socialization by using customary institutions to move the community to be aware of their ancestral heritage so that they continue the tradition. The distribution of the Pantauan Bunting tradition varies in each region due to geographical and social factors. Even though it has entered the modern era, the existence of this tradition is still maintained by the Besemah people and we can still find it in various areas in Lahat Regency.